PERAN KEPALA MADRASAH DALAM MEMBANGUN MADRASAH UNGGUL - Pratama, Wahyu Adji; Winaryo, Slamet; Ernawatie (Equity In Education Journal, 2024)
This study aims to describe the role of the principal in building a superior madrasah at MTsN 1 Palangka Raya. This research is a qualitative research with a case study design. Data were collected through observation, interview, and documentation study. Data analysis went through the stages of data condensation, data presentation, and conclusion drawing/verification. Source triangulation was conducted to validate the data. The results showed that the role of the madrasah head as a manager, motivator, and entrepreneur was good with the realization of a clear and measurable school work program, able to motivate all school members, and able to cooperate with outside the school in an effort to improve quality and build a superior madrasah at MTsN 1 Palangka Raya.